2021
DOI: 10.1039/d1cp02840e
|View full text |Cite
|
Sign up to set email alerts
|

High time resolution measurements of droplet evaporation kinetics and particle crystallisation

Abstract: A refined technique for observing the complete evaporation behaviour of free-falling droplets, from droplet generation to complete solvent evaporation, with ultra-high time resolution is introduced and benchmarked. High-resolution phase-delay stroboscopic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…Interestingly, the salt crystals formed are smaller and more numerous as the RH is lowered ( SI Appendix , Fig. S6 ), consistent with previous work that has shown that there is a greater propensity for nucleation when droplets are dried at higher rates leading to more nucleation events and smaller final crystals forming a larger composite particle ( 61 ).…”
Section: Resultssupporting
confidence: 90%
“…Interestingly, the salt crystals formed are smaller and more numerous as the RH is lowered ( SI Appendix , Fig. S6 ), consistent with previous work that has shown that there is a greater propensity for nucleation when droplets are dried at higher rates leading to more nucleation events and smaller final crystals forming a larger composite particle ( 61 ).…”
Section: Resultssupporting
confidence: 90%
“…The particles exhibit the same trends shown by Hardy et al, with fast-drying droplets resulting in crusts comprising higher numbers (∼10) of smaller (≤5 μm diameter) crystals and particles formed from slower drying made of a smaller number of crystals which are larger. 26 In the case of droplets drying close to the efflorescence RH (35 and 40% RH), droplets produce a single large (∼15 μm diameter) crystal. Between these extremes in RH a more diverse range of morphologies is observed, which may be due to the stochastic nature of particle nucleation and the window of crystallization that broadens with decreased evaporation rate.…”
Section: Resultsmentioning
confidence: 99%
“…The FDC has been introduced in detail previously, so here we just outline the main components. 26 Individual droplets are generated at a regular frequency (10s of Hz) using a DoD dispenser. The droplets propagate down through a vertical column in line with a gas flow of controlled flow rate and RH, as indicated in Figure 3 .…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the typical time scale of droplet-to-particle conversion in high-temperature flames can be extremely short (usually on the order microseconds), making it difficult to investigate the evaporation process merely based on experimental instruments. 8,13 Besides, in an FSP experiment, it is challenging to isolate the droplet evaporation process for examination, as the solvent evaporation may be coupled with other processes during the droplet-to-particle conversion, such as collisions of the droplets, thermal decomposition of the solute, particle inception, etc. In this regard, as a complement to current experimental techniques, the molecular dynamics (MD) simulation method presents to be a powerful tool to provide atomic insights into the droplet evaporation process in the context of FSP synthesized NCM materials.…”
Section: Introductionmentioning
confidence: 99%